The Influence of Product Innovation on Marketing Performance through Competitive Advantage in Rattan MSMEs in Cirebon Regency - Yuli Indriyani; Soesanty Maulany; Misbak Misbak (International Journal Labs, 2026)
Rattan MSMEs in Cirebon Regency play a significant role in supporting Indonesia’s handicraft industry and contributing to national export performance. However, increasing global competition, changing consumer preferences, and market uncertainty continue to challenge the ability of these enterprises to maintain sustainable marketing performance. Therefore, this study aims to analyze the influence of product innovation on marketing performance with competitive advantage as a mediating variable. A quantitative approach with a causal associative research design was employed. The study involved 102 rattan MSMEs selected from a population of 136 business units using the Slovin sampling technique. Data were collected through structured questionnaires using a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The findings indicate that product innovation has a positive and significant effect on both competitive advantage and marketing performance. In addition, competitive advantage significantly influences marketing performance and serves as a mediating variable in the relationship between product innovation and marketing performance. These results suggest that continuous product innovation can strengthen the competitive position of rattan MSMEs, which in turn improves their marketing performance. The study provides practical implications for MSME managers in developing innovation-driven strategies to achieve sustainable competitiveness and business growth.